Jejaring Wacana Cuitan Twitter pada Kontroversi Konten Pemeliharaan Satwa Liar - H. Zunaedi, Zuraida Zein (PERSPEKTIF, 2024)
This research seeks to understand the dynamics of controversy over wildlife preserving content on Twitter and how various actors voice their arguments on this issue. This research focuses on the process of argumentative discourse in the controversy over wildlife care content on Twitter. 353 tweets were found which produced 476 statements and 32 concepts summarized in four categories. The discourse that emerges is dominated by discourse voiced by actors who oppose the content of preserving wild animals. The first category is the reasons for not keeping and watching wildlife are consists of nine concepts. The second category, the reasons for maintaining and producing wildlife content, consists of seven concepts. The third category is the effects of keeping wildlife content consists of 3 concepts. Finally, the education category consists of six concepts. The results of this research show that netizens have the highest frequency of participation in voicing their opinions regarding the controversy over the content of wildlife conservation even without professional experience in the field of wildlife conservation. Apart from that, netizens have an important role in influencing the public's voice on this issue.